PENGARUH SELF MONITORING TERHADAP IMPULSE BUYING PADA REMAJA PEREMPUAN DALAM PEMBELIAN PRODUK TAS REPLIKA - Christie Devita (Ma Chung Press, 2015)
Consumptive behavior on adolescence growing rapidly because they want to live a luxury life, particularly for bag, as an indicator to shows their social status. However, some of them did not get the luxury life they want, that’s because the luxury goods cost more than they can afford. Otherwise, they choose to buy a replica bag from the famous and well-known brands which is cheaper than the authentic one. This quantitative research analyzed the relation of self monitoring with impulsive behavior on teenage girl towards purchasing product on replica bag. Self monitoring has 3 (three) indicators and impulse buying has 8 (eight) indicators. This research involve 201 (two hundred and one) respondent. The respondent consist of teenage girl with age range 18-21 years old, have never bought an authentic bag, and domicile in Malang and Surabaya. The significance of this study is giving a reference for further research with the same topic. The practical implication of this research is expected that it can be used as information for people, replica bag manufacturer, and the authentic bag manufacturer. In short, suggestion for the authentic bag manufacturer: knowing teenager financial condition which is different from the adult, and for the replica bag manufacturer: knowing people understanding about impulse buying as it related with self monitoring on teenager, and for further researcher: to expand this research by adding more variable (shopping life style or fashion involvement).